Barriers to Achieving Economies of Scale in Analysis of EHR Data - Sendak, Mark P.; Balu, Suresh; Schulman, Kevin A. (Applied Clinical Informatics, 2017)
Signed in 2009, the Health Information Technology for Economic and Clinical Health Act infused $28 billion of federal funds to accelerate adoption of electronic health records (EHRs). Yet, EHRs have produced mixed results and have even raised concern that the current technology ecosystem stifles innovation. We describe the development process and report initial outcomes of a chronic kidney disease analytics application that identifies high-risk patients for nephrology referral. The cost to validate and integrate the analytics application into clinical workflow was $217,138. Despite the success of the program, redundant development and validation efforts will require $38.8 million to scale the application across all multihospital systems in the nation. We address the shortcomings of current technology investments and distill insights from the technology industry. To yield a return on technology investments, we propose policy changes that address the underlying issues now being imposed on the system by an ineffective technology business model.Citation: Sendak MP, Balu S, Schulman KH. Barriers to Achieving Economies of Scale in Analysis of EHR Data. Appl Clin Inform 2017; 8: 826–831 https://doi.org/10.4338/ACI-2017-03-CR-0046
Keywords: Chronic Kidney Diseases; Health Services Research; Informatics; Primary Health Care